ALK and ROS1 Overexpression is Very Rare in Colorectal Adenocarcinoma. Issue 2 (February 2015) - Houang, Michelle; Toon, Christopher W.; Clarkson, Adele; Sioson, Loretta; de Silva, Keshani; Watson, Nicole; Singh, Nisha R.; Chou, Angela; Gill, Anthony J.
<x xml:space="preserve">Abstract</x> Crizotinib, a small molecule tyrosine kinase inhibitor, has shown tremendous promise in the treatment of lung adenocarcinomas harboring either ALK or ROS1 rearrangements. Recently, small studies of colorectal carcinomas (CRCs) have suggested an incidence of EML4-ALK translocations of 0.4% to 2.4% and FIG-ROS1 translocations of 0.8%. In lung cancer, screening immunohistochemical staining for ALK and ROS1 has been validated as highly sensitive for these translocations, but this has not been investigated in CRC. We therefore sought to investigate the incidence of ALK and ROS1 overexpression as detected by immunohistochemical staining in a large cohort of CRCs. Of the 1889 CRCs, only 1 case (0.05%) demonstrated diffuse strong positive staining for ALK, whereas 14 (0.7%) showed weak nonspecific staining; the remainder were negative. The 1 positive case was confirmed to harbor an ALK rearrangement by fluorescent in situ hybridization (FISH), whereas the 14 tumors with weak staining were FISH-negative. The ALK positive case demonstrated positive expression in all dysplastic and malignant cells indicating that the translocation was an early clonal event. No cases were positive for ROS1 by immunohistochemical staining, although 2 cases did show some nonspecific staining and were shown to be negative for ROS1 translocation by FISH. We conclude that although diffuse strong positive staining for ALK is likely to be highly specific for ALK rearrangement in CRC, both ALK and ROS1 immunohistochemical staining are very low-yield tests and difficult to justify in the routine clinical setting.